The Disciplinary Order and its Contrary: Popular Music and Gender Relations - Paranhos, Adalberto (Pontifícia Universidade Católica de São Paulo, 2005)
Frequently seen with binopulars, the  Estado Novo —as assessed by many analysts—seems to have been successful in its attempt to mold Brazilian society to its ownimage. Against these analyses, this article ventures into the world of popular musicproduced during that time and seeks to revive some voices out off keeping withofficial discourses, especially in the area of gender relations.